The relationship between vitamin E and C intake with total activity of erythrocytes and breast milk superoxide dismutase in lactating mothers - Ninik Mudjihartini; Diyah Eka Andayani; Sheira Taflah Putri Handana (Acta Biochimica Indonesiana, 2021)
Background: Human milk contains many components, one of them is superoxide dismutase (SOD). Vitamin E and C, together with SOD, can prevent oxidative stress. Objective: This study investigated the correlation between vitamin E and vitamin C intake, with total SOD activity, in erythrocyte and breast milk among lactating mothers in Jakarta, Indonesia. Methods: Sixty lactating mothers aged 20–40 years were recruited in 1–6 months postpartum in Grogol Petamburan and the Cilincing Public Health Centre from March 2019 until April 2019. Vitamins E and C dietary intake were collected using a semi-quantitative food frequency questionnaire. SOD total activity of erythrocyte and breast milk was measured using the Ransod kit 125. Results: The median value of vitamin E intake was 6.50 mg/day, showing 91.7% of patients do not meet recommended daily intake (RDA) (19 gram/day), and the median of vitamin C intake was 120.05 mg/day with 70% participants fulfilling RDA. SOD total activity in erythrocyte and breastmilk showed a median value of 423.73 U/mL and 58.34 U/mL, respectively. The correlation between vitamin E intake with total SOD activity in erythrocyte (r = 0.143 p > 0,05) and breast milk (r = 0.041, p > 0,05) was not significant. Vitamin C intake was also not significantly correlated with SOD total activity in the erythrocyte. Conclusion: There is no significant correlation between vitamin E and vitamin C intake with the total activity of SOD of erythrocyte and breast milk in lactating mothers.